Effects of dopamine D1 and D2 receptor agonists on cognitive functions in rats - Zenko, Michelle J (University of Ottawa (Canada), 2009)
The dopamine system modulates many functions through its 5 G-protein-coupled receptors. Many studies have identified a synergy in gene expression, neuronal firing and stereotyped behaviours when the D1 and D2 dopamine receptors are concomitantly activated. This project aims to study the effects of co-administrating D1 and D2 agonists on various cognitive functions. Well established models were selected to evaluate cognitive functions: the Social Interaction Test of olfactory memory, the Delayed Non-Match-to-Sample T-Maze Test of working memory and the Active Avoidance Test of associative memory. We demonstrate that co-administration of D1 and D2 dopamine receptor agonists is deleterious to performance in olfactory and prefrontal-dependent working memory, but has no effects in striatal-dependent associative memory. The results of this study suggest a role, though detrimental, for the D1 and D2 dopamine receptor synergy in cognitive functions. Additional work will be necessary to properly characterize this role and its mechanism of action.
Keywords: Biology, Neuroscience.